CHILDREN’S RESPONSE TO THE UTTERANCES OF THEIR PARENTS’ NEGATION: COMMUNITIES IN KARTASURA - Kurniawan Kurniawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The act of obeying parents' right to control them or refusing the directives by challenging their parents’ authority are two preferences children may opt for. This present investigation concerns to what extend children respond upon hearing negative utterances aimed for them. This qualitative research applies a theory of speech acts proposed by Austin (1962) to analyze data classified as negation utterances. Four families living at the Kartasura become this research data source. To collect the data, the researcher implements direct observation by recording audio and taking notes on the parents and their children's interaction within a period of approximately an hour. The result of the study implies that mostly Kartasura children do what their parents tell them to do, while few data indicate children's refusal of parents’ negations. One reason is due to the cultural value held tightly and bequeathed by Javanese through a number of centuries that is the act to honor and obey parents’ directives. To sum up, the implementation of negative utterances in the parenting world is not prohibited; however, parents must keep in mind the use of proper portion.